2021
DOI: 10.1080/17429145.2021.1944676
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous γ-glutamic acid (GABA) induces proline and glutathione synthesis in alleviating Cd-induced photosynthetic inhibition and oxidative damage in tobacco leaves

Abstract: The effects of exogenous γ-glutamic acid (GABA) on photosynthetic gas exchange capacity, PSII function, proline (Pro) synthesis and ROS metabolism of tobacco leaves under cadmium (Cd) stress were studied. The results showed that both stomatal and non-stomatal factors were the important factors to limit the photosynthetic capacity of tobacco leaves under Cd stress. Pro accumulation and glutathione (GSH) content increase are the important ways for tobacco leaves to adapt to Cd stress. Exogenous GABA significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 84 publications
0
4
1
Order By: Relevance
“…This study showed that GABA supplementation to the root zone improved Cd accumulation in C. grandiflora ( Figure 1 C,D), which indicated that GABA acts as a soil amendment. The results were different from previous findings that foliar spraying of exogenous GABA [ 18 ] and its addition in hydroponics [ 14 , 15 ], semihydroponics [ 16 ], or nutrient media [ 13 ] reduced HM uptake by plants. A similar phenomenon has also been observed for cysteine, for example, which increased Cd accumulation in Solanum nigrum in soils [ 19 ] and Hg accumulation in Arabidopsis in Hoagland nutrient solution [ 20 ] but reduced Cr uptake in B. napus in MS media [ 21 ] and in maize shoots in Hoagland nutrient solution [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed that GABA supplementation to the root zone improved Cd accumulation in C. grandiflora ( Figure 1 C,D), which indicated that GABA acts as a soil amendment. The results were different from previous findings that foliar spraying of exogenous GABA [ 18 ] and its addition in hydroponics [ 14 , 15 ], semihydroponics [ 16 ], or nutrient media [ 13 ] reduced HM uptake by plants. A similar phenomenon has also been observed for cysteine, for example, which increased Cd accumulation in Solanum nigrum in soils [ 19 ] and Hg accumulation in Arabidopsis in Hoagland nutrient solution [ 20 ] but reduced Cr uptake in B. napus in MS media [ 21 ] and in maize shoots in Hoagland nutrient solution [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…5). Earlier ndings have also demonstrated that GABA down regulates oxidative biomarkers hence signi cant improvement in the functioning of photosynthetic apparatus in tomato and brinjal seedlings under arsenic stress (Suhel et al 2022) and in tobacco (He et al 2021) under Cd stress by substantial reduction in oxidative stress. Likewise, MeJA also plays an important role in Cd toxicity alleviation on structure and function chloroplast in Pisum sativus L. (Manzoor et al 2022) and Mentha arvensis (Zaid et al 2018) exposed to Cd stress by decreasing oxidative damage.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies suggest that GABA may enhance the uptake of calcium [ 91 ], magnesium [ 92 ], and potassium [ 93 ] during metal stress. GABA application to different plants like mustard [ 30 ], rice [ 41 ], tobacco [ 35 ], and maize [ 84 ] increases these minerals uptake and transport during metal stress conditions, thereby potentially mitigating the detrimental effects of metal toxicity on plant physiology and overall growth.…”
Section: Discussionmentioning
confidence: 99%
“…GABA applied exogenously improves amino acid contents, reduces cadmium (Cd 2+ ) uptake, and improves GABA-related gene expression [ 34 ]. Research has demonstrated that glutamate decarboxylase ( GAD ) stands out as the most responsive gene associated with GABA metabolism when it comes to reacting to abiotic stress [ 35 ]. The activity of the GAD enzyme and the expression of its associated genes are intricately linked to the improvement of plant stress resistance through GABA mediation [ 36 ].…”
Section: Introductionmentioning
confidence: 99%